Indian clinical practice consensus guidelines for the management of oropharyngeal cancer - Prabhash, Kumar; Babu, Govind; Chaturvedi, Pankaj; Kuriakose, Moni; Birur, Praveen; Anand, Anil; Kaushal, Ashish; Mahajan, Abhishek; Syiemlieh, Judita; Singhal, Manish; Gairola, Munish; Ramachandra, Prakash; et al. (Indian journal of cancer, 2020)
Diagnosis Workflow for Evaluation of Clinical Stages Human papillomavirus (HPV) is associated with oropharyngeal squamous cell carcinoma (SCC) and p16 staining is used to predict the HPV status and prognosis. HPV testing is recommended for testing (1) newly diagnosed oropharyngeal SCC, nontobacco users (males/females), patients with high-risk sexual behavior, early T-stage with advanced N-stage, cystic nodal metastasis on radiological imaging, nonkeratinizing or basaloid SCC, and carcinoma unknown primary with neck nodes. High-risk patients (EL 1; Grade A) may be treated with three alternative options: (i) conventional fractionation (66 Gy [2.2 Gy/fraction] to 70 Gy [2.0 Gy/fraction]; daily, Monday–Friday in 6–7 weeks), (ii) concomitant boost accelerated RT (72 Gy/6 weeks [1.8 Gy/fraction, large field; 1.5 Gy boost as second daily fraction during last 12 treatment days] or 66–70 Gy [2.0 Gy/fraction]; 6 fractions/week accelerated), or (iii) hyperfractionation (81.6 Gy/7 weeks [1.2 Gy/fraction, twice daily]), while low-to-intermediate risk (IIB) patients can be given 44–50 Gy (2.0 Gy/fraction) to 54–63 Gy (1.6–1.8 Gy/fraction) of radiation.